Impact of Servant Leadership on Performance: The Mediating Role of Affective and Cognitive Trust - Saleem, Farida; Zhang, Yingying Zhang; Gopinath, C.; Adeel, Ahmad (SAGE open, 2020)
Servant leadership style has drawn much attention in the last decade to leadership studies on account of its focus on serving others first. Extant literature calls for a better understanding of the underlying mechanism for servant leadership to positively influence performance within an organization. We position servant leadership to contribute to firms’ sustainable performance, by empirically studying the mediating mechanism of bi-dimensional trust, namely affective and cognitive trust, between servant leadership and individual performance. Our data comprised of dyadic samples of 233 pairs of subordinates and their supervisors. The results from hierarchical linear model (HLM) for clustered data showed that servant leadership strongly predicted affective trust, organizational citizenship behaviors (OCBs), and task performance of subordinates; affective trust fully mediated servant leadership’s effect on task performance while partially mediates servant leadership’s effect on subordinates’ OCB. In contrast, cognitive trust did not mediate servant leadership’s effect on either OCB or task performance. These findings reveal the relevance of affective trust as the underlying mechanism which mediates and deciphers servant leadership into positive individual performance.